Digital Marketing Strategies for Seaweed SMEs in South Sulawesi: An Application of the Technology Acceptance Model (TAM) - Andi Putri Tenriyola; Nurfaisah Baharuddin; Tri Desi Lestari; Anis Anshari Mas'ud (Jurnal Manajemen dan Kewirausahaan, 2024)
This research expands the existing body of knowledge on e-commerce adoption among small and medium-sized enterprises (SMEs) by examining seaweed businesses in South Sulawesi, Indonesia, through the lens of the Technology Acceptance Model (TAM). The objective is to identify the factors influencing e-commerce adoption among seaweed SMEs, focusing on perceived ease of use, perceived usefulness, and self-efficacy. The study employs a quantitative approach, utilizing surveys distributed to seaweed business operators. Structural Equation Modeling (SEM) is used for data analysis to validate the relationships between the constructs proposed in the TAM framework. The findings reveal a significant positive relationship between perceived ease of use and e-commerce adoption. Furthermore, perceived usefulness and self-efficacy are identified as key mediators that enhance e-commerce adoption. This study also emphasizes the critical role of user attitude in mediating the relationship between ease of use, usefulness, self-efficacy, and e-commerce adoption. The results underscore the importance of raising awareness and understanding of e-commerce benefits among SMEs. Businesses should focus on providing high-quality, relevant information to boost user confidence and adoption rates. Consequently, this study makes a substantial contribution to the literature on digital management and marketing, offering practical guidance for SMEs to effectively leverage e-commerce.